1989
DOI: 10.1111/j.1600-0773.1989.tb00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpromazine, Administered in Vivo and in Vitro, Inhibits the Efflux of Bile Acids in Freshly Isolated Rat Hepatocytes*

Abstract: Although it has been speculated that chlorpromazine may alter the transhepatic movement of bile acids from plasma to bile, the effect of chlorpromazine on various determinants of bile acid transport in isolated rat hepatocytes remains incompletely defined. In particular, there is little information about the effect of chlorpromazine on the release of bile acids from freshly isolated hepatocytes. Therefore, we examined the effect of chlorpromazine, administered in vivo and in vitro, on the efflux rate of radiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, also with isolated cells it is uncertain to localize efflux phenomena to a distinct cell pole. The efflux from isolated cells was decreased when the cells were prepared from rat livers of cholestatic animals, achieved either by bile duct ligation or ethinylestradiol treatment (Tarao et al 1982), and when rats were pretreated by the cholestatic compound chlorpromazine (Willson et al 1989). This indicates that cholestatic cell perturbations prevail even during the isolation procedure, and that single cells may be used in cholestasis research.…”
Section: Export At the Sinusoidal Membranementioning
confidence: 99%
“…However, also with isolated cells it is uncertain to localize efflux phenomena to a distinct cell pole. The efflux from isolated cells was decreased when the cells were prepared from rat livers of cholestatic animals, achieved either by bile duct ligation or ethinylestradiol treatment (Tarao et al 1982), and when rats were pretreated by the cholestatic compound chlorpromazine (Willson et al 1989). This indicates that cholestatic cell perturbations prevail even during the isolation procedure, and that single cells may be used in cholestasis research.…”
Section: Export At the Sinusoidal Membranementioning
confidence: 99%
“…Therefore, hepatotoxicity by CPZ represents a realistic health risk for humans which should not be ignored [ 13 ]. Experimental studies revealed that CPZ inhibits bile flow in perfused rat livers [ 14 ] and freshly isolated rat hepatocytes [ 15 ], a mechanism associated with bile acid accumulation which likely contributes to cholestasis in animals and humans [ 16 ]. Furthermore, CPZ-induced hepatotoxicity involves the sustained activation of the c-Jun N-terminal kinases (JNKs) pathway of cellular stress [ 17 ], oxidative stress [ 18 ], cell-to-cell junction disruption and release of pro-inflammatory cytokines [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, hepatotoxicity by CPZ represents a realistic health risk for humans which should not be ignored [13]. Experimental studies revealed that CPZ inhibits bile ow in perfused rat livers [14] and freshly isolated rat hepatocytes [15], a mechanism associated with bile acid accumulation which likely contributes to cholestasis in animals and humans [16]. Furthermore, CPZ-induced hepatotoxicity involves the sustained activation of the c-Jun N-terminal kinases (JNKs) pathway of cellular stress [17], oxidative stress [18], cell-to-cell junction disruption and release of pro-in ammatory cytokines [19].…”
Section: Introductionmentioning
confidence: 99%